1992
DOI: 10.1038/ng0492-34
|View full text |Cite
|
Sign up to set email alerts
|

Automated DNA sequencing and analysis of 106 kilobases from human chromosome 19q13.3

Abstract: A total of 116,118 basepairs (bp) derived from three cosmids spanning the ERCC1 locus of human chromosome 19q13.3 have been sequenced with automated fluorescence-based sequencers and analysed by polymerase chain reaction amplification and computer methods. The assembled sequence forms two contigs totalling 105,831 bp, which contain a human fosB proto-oncogene, a gene encoding a protein phosphatase, two genes of unknown function and the previously-characterized ERCC1 DNA repair gene. This light band region has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…The 3© end of the cDNA was also determined by RACE using essentially the same protocol except that the dT anchor primer was used rather than oligo(dT) to prime the first-strand cDNA. The appropriate cDNA sequence-specific primers were designed from the published sequence corresponding to the open reading frame (ORF) of ASE-1 (Van Duin et al 1989;Martin-Gallardo et al 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3© end of the cDNA was also determined by RACE using essentially the same protocol except that the dT anchor primer was used rather than oligo(dT) to prime the first-strand cDNA. The appropriate cDNA sequence-specific primers were designed from the published sequence corresponding to the open reading frame (ORF) of ASE-1 (Van Duin et al 1989;Martin-Gallardo et al 1992).…”
Section: Methodsmentioning
confidence: 99%
“…This autoantigen is localized to the FCs of the nucleolus during interphase and the NORs of the chromosomes during cell division. This cDNA encompasses a previously identified open reading frame, ASE-1 (Van Duin et al 1989;Martin-Gallardo et al 1992), which is positioned in an antisense orientation to and overlaps the gene for the DNA excision repair enzyme ERCC-1 (Van Duin et al 1986). …”
Section: Introductionmentioning
confidence: 98%
“…The Huntington disease region in chromosome 4p16.3 showed 26 islands in w740 kb, which gives an average of 1 every -28 kb (20,29,30). An analysis of the ERCCI locus of human chromosome 19q13.3 has detected 6 islands in 106 kb of DNA, representing an average of about 1 in 18 kb (19). Another 6 islands have been mapped in a 180-kb region in human chromosome 10q11.2 at a region tightly linked to the gene responsible for multiple endocrine neoplasia type 2A.…”
Section: Methodsmentioning
confidence: 99%
“…Our estimate depends on the assumption that each CpG island identifies a gene. While it is possible that some are not associated with genes (18), the number is likely to be small, as gene mapping studies across long chromosome regions have shown that novel CpG islands are usually associated with transcripts (19,20). In a few cases genes with two associated CpG islands have been reported (5).…”
Section: Methodsmentioning
confidence: 99%
“…1B for the case of the 32 pairs of complementary trinucleotides in the 68-kb GenBank sequence HUMMMDBC (Martin-Gallardo et al 1992). The frequency of one member of each of the pairs is plotted relative to the Y-axis and the frequency of the corresponding member relative to the X-axis.…”
Section: Methodsmentioning
confidence: 99%